Serum Biochemical Changes During Transportation Stress in Adult Goats - Panchal, Pooja; Dalvi, Santosh; Ambade, Ravindra; Dighe, Dhananjay; Deshmukh, Rahul (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
A study was conducted to evaluate the effect of short journey transportation stress on the serum biochemical parameters in adult goats.  Fifty healthy adult goats irrespective of sex, age and breed were transported for about 200 km from Ahmednagar district of Maharashtra  (India) to Thane district of Maharashtra (India), by road without feed and water during transportation. Blood samples were collected  from these goats before loading and after unloading at destination and thereafter for next two weeks. The biochemical parameters were  estimated using standard biochemical kits. The levels of biochemical parameters viz. total proteins, albumin, globulin, total calcium,  phosphorus and glucose were significantly (p
Keywords: Biochemical Changes; Goats; Transportation stress